The Position of the Regent's Circular Letter Regarding Village Regulations in Legislation - Sri Sudono Saliro; Muslimah Muslimah; Mualimin Mualimin (Jurnal Wawasan Yuridika, 2023)
The purpose of this study is to determine with certainty the position of the Regent'sCircular Letter, and legal implications arising from the Regent's Circular Letter againstVillage Regulations. This paper study is descriptive analysis in nature, and the type ofstudy is normative juridical with the statutory approach method. The type of data usedis secondary data and the method of collecting it uses library study and interviews. Thecollected data is processed and analyzed qualitatively in order to arrange systematicsentences based on the order of the problem. The research findings reveal that theRegent's Circular is a policy regulation and not a statutory regulation. Although in itsimplementation it is positioned as an official document containing instructions fromthe local government to the village government as a subsystem of government. Thelegal consequence is that it cannot be included as a consideration considering andconsidering the formation of village regulations.